Analisis Peran Lembaga Keuangan Dalam Peningkatan Akses Modal Usaha Kecil Dan Menengah Pada UMKM Karawang - Amalia Amalia; Sungkono Sungkono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to analyze the role of financial institutions in improving access to capital for Micro, Small, and Medium Enterprises (MSMEs) in Karawang, as well as to identify barriers faced by MSMEs in accessing financial services. A descriptive quantitative method was used using a questionnaire as a data collection tool. The research focused on the role of financial institutions in providing access to capital to MSMEs, the constraints faced by MSMEs in accessing capital from financial institutions, and the effectiveness of financial programs and products offered by financial institutions in helping MSMEs obtain the required capital. The results of the study are expected to provide a deeper understanding of the important role of financial institutions in supporting the growth of MSMEs in Karawang. Through the analysis of quantitative data obtained from questionnaires, constraints faced by MSMEs can be clearly identified, thus providing a basis for financial institutions and the government to design more effective policies. In addition, the effectiveness of programs and financial products offered can be evaluated to improve access to capital for MSMEs. By understanding the dynamics between MSMEs and financial institutions in Karawang, this research is expected to provide useful recommendations for policy makers and financial practitioners in improving the quality of access to finance for MSMEs, thereby supporting more inclusive and sustainable local economic growth.